China's transportation energy consumption and CO2 emissions from a global perspective. (July 2015) - Yin, Xiang; Chen, Wenying; Eom, Jiyong; Clarke, Leon E.; Kim, Son H.; Patel, Pralit L.; Yu, Sha; Kyle, G. Page
Abstract: Rapidly growing energy demand from China's transportation sector in the last two decades have raised concerns over national energy security, local air pollution, and carbon dioxide (CO2 ) emissions, and there is broad consensus that China's transportation sector will continue to grow in the coming decades. This paper explores the future development of China's transportation sector in terms of service demands, final energy consumption, and CO2 emissions, and their interactions with global climate policy. This study develops a detailed China transportation energy model that is nested in an integrated assessment model—Global Change Assessment Model (GCAM)—to evaluate the long-term energy consumption and CO2 emissions of China's transportation sector from a global perspective. The analysis suggests that, without major policy intervention, future transportation energy consumption and CO2 emissions will continue to rapidly increase and the transportation sector will remain heavily reliant on fossil fuels. Although carbon price policies may significantly reduce the sector's energy consumption and CO2 emissions, the associated changes in service demands and modal split will be modest, particularly in the passenger transport sector. The analysis also suggests that it is more difficult to decarbonize the transportation sector than other sectors of the economy, primarily owing to its heavy reliance on petroleum products. Highlights: Transport sector in China are analyzed from a global perspective. Passenger transport turnover reduction and modal shifts is less sensitive to carbon price. Bio-fuel, electricity and H2 will play an important role for carbon mitigation in transport sector. The transport sector is more difficult to decarbonize than other sectors.